(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Managing psychiatric medications is a crucial aspect of mental health care, and nurses play a pivotal role in patient education and support in this domain. This abstract provides an overview of the nurse’s role in medication management, emphasizing the importance of comprehensive patient education, individualized treatment plans, side effect management, adherence promotion, patient empowerment, and collaborative care.